Managing Environmental Challenges Using Environmental Management Accounting: A Case of Food Manufacturing Companies in Gauteng Province of South Africa - Emmanuel Obinali OBIOHA; Jacob Karabo ZULU (PT Keberlanjutan Strategis Indonesia, 2025)
Substantial resources have been lost and human and societal wellbeing endangered due to the environmental challenges/impacts in the food and beverage manufacturing companies in Gauteng. The focus of this paper therefore, is to establish the potential environmental problems/impacts prevalent in food and beverage companies and to determine how environmental management accounting physical and monetary systems can address these problems. Quantitative techniques were utilized to collect numerical, non-numerical and unstructured data through analytical contacts and qualitative data was collected via annual reports, processes and policies in place in food and beverage companies of Gauteng listed in Johannesburg Stock Exchange subscribing to Socially Responsibility Investment index and ISO 14000. Documents analysis, was used to validate the literature and the data from questionnaire. Data was analysed statistically by employing a computer package called Stata V15 software and summarised in the form of absolute and relative frequencies. Cronbach's alpha tested for internal validity/consistency and reliability. The findings revealed environmental challenges/impacts like input-output balance, pollution, waste and emission generations, recycling of material and environmental costs at Gauteng food manufacturing companies of South Africa. Managerial implication is that these challenges/impacts could be prevented/reduced via full/proper application of environmental management accounting systems at source. The study thus, presents environmental management accounting to literature as a system/model for achieving strategic advantages, environmental and financial sustainability via capacity to monitor and manage the consumption and flow of energy, water, material and waste more accurately in food manufacturing companies or other industrial sectors in South Africa or the world.